2009
DOI: 10.1111/j.1364-3703.2009.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen profile update: Fusarium oxysporum

Abstract: http://www.broad.mit.edu/annotation/genome/fusarium_group/MultiHome.html; http://www.fgsc.net/Fusarium/fushome.htm; http://www.phi-base.org/query.php

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
488
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 646 publications
(505 citation statements)
references
References 134 publications
(171 reference statements)
9
488
0
8
Order By: Relevance
“…These diseases are caused by fungi in the phylum ascomycota that also includes F. oxysporum, A. nidulans, and S. cerevisiae. Some F. oxysporum strains are also known pathogens of these diseases (43). Because the glutathione system is conserved among these fungi, our finding that it detoxify elemental sulfur impacts the physiology of fungal pathogens treated with elemental sulfur fungicide, as well as future applications in controlling fungal pathogens.…”
Section: Discussionmentioning
confidence: 93%
“…These diseases are caused by fungi in the phylum ascomycota that also includes F. oxysporum, A. nidulans, and S. cerevisiae. Some F. oxysporum strains are also known pathogens of these diseases (43). Because the glutathione system is conserved among these fungi, our finding that it detoxify elemental sulfur impacts the physiology of fungal pathogens treated with elemental sulfur fungicide, as well as future applications in controlling fungal pathogens.…”
Section: Discussionmentioning
confidence: 93%
“…Fusarium oxysporum is a root-infecting fungal pathogen that causes wilt disease on a broad range of economically important plant species and also the model plant Arabidopsis (Arabidopsis thaliana; Dombrecht et al, 2006;van Hemelrijck et al, 2006;Berrocal-Lobo and Molina, 2008;Michielse and Rep, 2009). This pathogen is soilborne and enters the plant initially through the roots, and subsequently colonizes the vascular tissues and xylem vessels before moving up to stem and foliar tissues (Lagopodi et al, 2002;Czymmek et al, 2007).…”
mentioning
confidence: 99%
“…Studies revealed that the general pattern of colonization in soil was similar for the pathogenic strain and Fo47. However, Fo47 grew faster than the pathogenic strain and, as a consequence, colonized the rhizosphere earlier (Michielse and Rep, 2009). …”
Section: Consider Addition Of Non-antagonistic Microbes Into the Biocmentioning
confidence: 99%